Structural breaks, international tourism development and economic growth. Issue 1 (1st January 2019) - Yazdi, Soheila Khoshnevis
Abstract: This study examines the causal relationships between tourism, physical capital, human capital, household consumption expenditure and economic growth for the period 1981–2014 using Structural Breaks tests, Autoregressive Lag (Distributed A.R.D.L.) approach and Granger causality test. There is one cointegrating relationship between these variables, while the V.E.C.M. comprises both a short- and long-run relation. Tourism has a negative impact on Iranian's economic growth both in the short- and long-run. The results showed there is unidirectional causality running from international tourism to economic growth. Our findings have also empirically verified the presence of the Tourism-Led Growth Hypothesis (T.L.G.H.) in Iran. Tourism could be an effective substance for the growth of the Iranian economy. They showed that tourism is in part an endogenous growth process, requiring a systematic allocation of resources to sustain its development for local and regional economies.